PENGENTASAN KEMISKINAN MELALUI USAHA INDUSTRI KECIL MENENGAH DI KABUPATEN MAGELANG - Dinar Melani Hutajulu; Fitrah Sari Islami; Rian Destiningsih (Politeknik Bisnis Indonesia, 2021)
The poverty condition in Magelang Regency is still considered high, reaching 10.67 percent of the total population in Magelang Regency. This number still lags behind the national average of 9.41 percent. This is also not in accordance with the 2014-2019 RPJMD target of Magelang Regency where the percentage of poverty is expected to touch 9 percent. The purpose of this study was to determine how small and medium industrial enterprises influence poverty alleviation in Magelang Regency. The research was conducted in Magelang Regency using secondary data for 20 years from 2000 - 2019. The method of analysis used ordinary least squares. The results show that all variables have a simultaneous effect on poverty alleviation efforts in Magelang Regency. However, partially, there are only a few variables that have an influence on poverty alleviation, such as the total of SMIEs, SMIEs employment and the investment value of SMIEs.